The Structure and Function of the Gram-Positive Bacterial RNA Degradosome - Cho, Kyu Hong (Frontiers in Microbiology, 2017)
The RNA degradosome is a highly structured protein complex responsible for bulk RNA decay in bacteria. The main components of the complex, ribonucleases, an RNA helicase, and glycolytic enzymes are well conserved in bacteria. Some components of the degradosome are essential for growth and the disruption of degradosome formation causes slower growth, indicating that this complex is required for proper cellular function. The study of the E. coli degradosome has been performed extensively for the last several decades and has revealed detailed information on its structure and function. On the contrary, the Gram-positive bacterial degradosome, which contains ribonucleases different from the E. coli one, has been studied only recently. Studies on the Gram-positive degradosome revealed that its major component RNase Y was necessary for the full virulence of medically important Gram-positive bacterial pathogens, suggesting that it could be a target of antimicrobial therapy. This review describes the structures and function of Gram-positive bacterial RNA degradosomes, especially those of a Gram-positive model organism Bacillus subtilis, and two important Gram-positive pathogens, Staphylococcus aureus and Streptococcus pyogenes.